Awareness, Attitudes, and Practices Regarding OTC Drugs in Circassian and Chechen Communities in Jordan: A Cross-Sectional Study - Qnais E; Barakat M; Alnajjar R; Alzaghari LF; Alqudah A; Dajani R; Hakooz N (Patient Preference and Adherence)
Esam Qnais,1 Muna Barakat,2 Roaa Alnajjar,3 Lujain F Alzaghari,2 Abdelrahim Alqudah,4 Rana Dajani,1 Nancy Hakooz5 1Department of Biology and Biotechnology, Faculty of Science, The Hashemite University, Zarqa, Jordan; 2Department of Clinical Pharmacy and Therapeutics, Faculty of Pharmacy, Applied Private University, Amman, Jordan; 3School of Pharmacy, The University of Jordan, Amman, Jordan; 4Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmaceutical Sciences, The Hashemite University, Zarqa, Jordan; 5Department of Biopharmaceutics and Clinical Pharmacy, School of Pharmacy, University of Jordan, Amman, JordanCorrespondence: Nancy Hakooz, Department of Biopharmaceutics and Clinical Pharmacy, School of Pharmacy, The University of Jordan, Amman, Jordan, Email nhakooz@ju.edu.joPurpose: Over-the-counter (OTC) medications are widely used for self-medication, yet their misuse can lead to adverse outcomes. This study aimed to assess the knowledge, awareness, and attitudes toward OTC drugs among Circassians and Chechens in Jordan.Methods: A cross-sectional study was conducted in September 2022 using an online survey targeting Circassians and Chechens aged 18 and above. The questionnaire was validated by clinical researchers and consisted of demographic data and questions on OTC drug use, awareness, and attitudes. Data from 418 participants were analyzed using descriptive and inferential statistics, with a significant level of p < 0.05.Results: The majority of participants were female (76.1%), married (78.5%), and almost half of the participants held a non-medical bachelor’s degree (49.3%). Analgesics (73.9%) and vitamins (56.7%) were the most used OTC drugs. Headache (65.6%), musculoskeletal pain (33.7%), and the common cold (25.4%) were the primary reasons for self-medication. Most participants (53.8%) expressed strong interest in knowing the side effects and contraindications of OTC drugs, while 72.5% checked expiry dates before use. Notably, 50.2% disagreed with the statement that OTC products have no side effects. Age and educational level were significantly associated with self-medication practices (p < 0.05).Conclusion: Circassians and Chechens in Jordan exhibit high awareness of the risks associated with OTC drug use, yet self-medication practices remain prevalent. Public health interventions should focus on education campaigns to mitigate potential misuse and promote safe practices. Keywords: over-the-counter drugs, self-medication, circassians and chechens, awareness and attitudes, jordanian population